Desenvolvimento de um sensor eletroquímico com nanopartículas de ouro e ftalocianina de cobre para a detecção de metais potencialmente tóxicos - Cuña, Leonardo José Quintero Da (2021)
Using the LbL self-assembly technique, an ITO electrode was modified with gold nanoparticles stabilized with PAH and copper phthalocyanines, for the detection of cadmium (Cd) and lead (Pb). Using the UV-Vis technique it was possible to monitor the film growth. The FTIR technique allowed us to observe the bands corresponding to PAH (3447 cm-1 due to NH+3) and CuTsPc (1024 cm-1 due to SO-3), responsible for the growth of the film. The electrochemical behavior of the sensor was evaluated with cyclic voltammetry, using an electrolyte solution containing 5 mmol L-1 of Paraquat and 0,1 mol L-1 KCl. Evaluating the reversibility criteria, it can be seen that the redox process is almost reversible and the mass transfer from the solution to the sensor surface is by diffusion. The Square Wave Anodic Stripping technique (SWAS) allowed the detection of Cd2+ and Pb2+ ions in the concentration range of 9.9 µg L-1 to 99 µg L-1. The analytical curves show two linear growths in this concentration range reaching detection limits of 3.7 µg L-1 for Cd2+ and 9.1 µg L-1 for Pb2+. From the analysis of real samples (drinking tap water) it can be concluded that the method is sensitive in the determination of these elements and can be used in the analysis of natural water samples. In general, the films showed satisfactory responses to analytes.